2022
DOI: 10.3389/fonc.2021.793653
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Postoperative Infectious Complications on Long-Term Outcomes for Patients Undergoing Simultaneous Resection for Colorectal Cancer Liver Metastases: A Propensity Score Matching Analysis

Abstract: ObjectiveTo investigate the impact of postoperative infectious complications (POI) on the long-term outcomes of patients with colorectal cancer liver metastasis (CRLM) after simultaneous resection of colorectal cancer and liver metastases.MethodsFour hundred seventy-nine CRLM patients receiving simultaneous resection between February 2010 and February 2018 at our hospital were enrolled. A 1:3 propensity score matching analysis (PSM) analysis was performed to balance covariates and avoid selection bias. After P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Infectious complications (IC) are among the most common adverse outcomes following PD. Additionally, evidence suggests that postoperative IC can affect oncologic outcomes for patients undergoing surgery for malignant disease 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infectious complications (IC) are among the most common adverse outcomes following PD. Additionally, evidence suggests that postoperative IC can affect oncologic outcomes for patients undergoing surgery for malignant disease 15 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, evidence suggests that postoperative IC can affect oncologic outcomes for patients undergoing surgery for malignant disease. 15 Currently, there are limited data regarding the influence of postoperative IC on patients undergoing surgery for malignant pancreatic diseases, particularly when such complications occur without clinically relevant postoperative pancreatic fistula (CR-POF). Consequently, this study aims to evaluate the effect of non-CR-POF-related postoperative IC on the OS of patients who have undergone PD for PDAC at a high-volume pancreatic center.…”
mentioning
confidence: 99%
“…Similarly, a foreign study showed that the incidence of postoperative infectious complications in patients with CRC was as high as 16.59% (4). Postoperative complications can lead to increased recurrence and mortality; moreover, Chen et al showed that in patients with CRC liver metastases, postoperative infectious complications were associated with worse progression-free survival (PFS) and overall survival (5).…”
Section: Introductionmentioning
confidence: 99%
“…A major concern regarding SR is the higher incidence of postoperative complications and their potential impact on long-term outcomes, and this has led to reluctance to perform SR [ 13 , 14 ]. Despite the attractiveness of the concept of the simultaneous excision of colon cancer and liver metastases, there is still a paucity of high-quality evidence.…”
Section: Introductionmentioning
confidence: 99%